2007
DOI: 10.1166/jnn.2007.330
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrated Forms of C60 Fullerene on Amyloid β-Peptide Fibrillization In Vitro and Performance of the Cognitive Task

Abstract: It has been shown for the first time by transmission electron microscopy that the hydrated fullerene C60 inhibited the fibrillization of amyloid-beta25-35 peptide. The fullerene affected the amyloid-beta25-35 assembly, manifesting its anti-amyloidogenic capacity. Our in vivo investigations demonstrated also that a single intracerebroventricular injection of the C60 hydrated fullerene at a dose of 7.2 nmol/ventricle significantly improved the performance of the cognitive task in control rats. The intracerebrove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(82 citation statements)
references
References 0 publications
5
77
0
Order By: Relevance
“…Spatial memory in adult rats was studied using a newlydeveloped probabilistic cognitive test in the Morris watermaze [20]. Briefly, in our test, rats were trained in a watermaze (140 cm in diameter) which was divided into eight virtual sectors and four virtual circles А, B, C, D ( Figure 3A).…”
Section: Behavioral Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial memory in adult rats was studied using a newlydeveloped probabilistic cognitive test in the Morris watermaze [20]. Briefly, in our test, rats were trained in a watermaze (140 cm in diameter) which was divided into eight virtual sectors and four virtual circles А, B, C, D ( Figure 3A).…”
Section: Behavioral Learningmentioning
confidence: 99%
“…However, in other studies, observed impairments of spatial memory were minor or not observed at all [19]. We have recently reported that the impairments of spatial memory in rats injected by Аβ [25][26][27][28][29][30][31][32][33][34][35] can be clearly observed using the newly-developed cognitive test in the Morris watermaze [20].…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated anti-assembly effect of C 60 hydrated fullerene (C 60 HyFn) on the fibrillization of Aβ [25][26][27][28][29][30][31][32][33][34][35] fragment . It was demonstrated that injection of 3.6 nMol of C 60 HyFn to each of the brain ventricles could prevent the cognitive impairment in rats previously injected with Aβ [25][26][27][28][29][30][31][32][33][34][35] fragment [43].…”
Section: Fullerenementioning
confidence: 99%
“…67 This phenomenon could have important implications for medical application of nanoparticles because the self-assembly of a variety of proteins and peptides is known to be the cause of human amyloid diseases where fibrous protein aggregates are formed, resulting in amyloid plaque deposition in the extracellular tissues. [68][69][70][71][72][73][74] Moreover, fibrillar structure seems to be related to heavy human disorders such as Alzheimer's disease, Parkinson's disease, and spongiform encephalopathies.…”
Section: Absorption Of Proteins On Nanoparticles Surfacementioning
confidence: 99%
“…For instance, there are nanosystems such as C60 hydrated fullerenes that can relax fibrillar structures. 60,68 Certainly, the control of the protein absorption on nanoparticle surfaces is an important issue to control their fate in biological systems. 75 In order to prevent or control the opsonization, several methods of disguising nanoparticles have been developed.…”
Section: Absorption Of Proteins On Nanoparticles Surfacementioning
confidence: 99%